2022
DOI: 10.1177/23969873221139695
|View full text |Cite
|
Sign up to set email alerts
|

Quality in stroke care during the early phases of the COVID-19 pandemic: A nationwide study

Abstract: Introduction: Evidence-based early stroke care as reflected by fulfillment of process performance measures, is strongly related to better patient outcomes after stroke and transient ischemic attack (TIA). Detailed data on the resilience of stroke care services during the COVID-19 pandemic are limited. We aimed to examine the quality of early stroke care at Danish hospitals during the early phases of the COVID-19 pandemic. Materials and methods: We extracted data from Danish national health registries in five t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…Knowledge on coronavirus infection status on a patient level did not influence care and the fulfilment of quality measures for patients with AIS admitted to a stroke unit. This is in line with previous results from a study on data from the DSR showing that the overall quality of care during the pandemic remained high 12. Similar studies from other countries, including the USA and UK, also found that quality in stroke care was maintained and for some domains even improved 26 27.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Knowledge on coronavirus infection status on a patient level did not influence care and the fulfilment of quality measures for patients with AIS admitted to a stroke unit. This is in line with previous results from a study on data from the DSR showing that the overall quality of care during the pandemic remained high 12. Similar studies from other countries, including the USA and UK, also found that quality in stroke care was maintained and for some domains even improved 26 27.…”
Section: Discussionsupporting
confidence: 91%
“…Information on 30-day mortality was obtained from the Danish Civil Registration System and information on quality of care was obtained from the DSR using the registered stroke care performance measures covering acute and prophylactic treatment, carotid vessel imaging and early rehabilitation. For each patient, we calculated an opportunity-based score defined as the number of fulfilled performance measures divided by the number of relevant performance measures as well as an all or no score, with a score of 1 if all relevant performance measures were met and a score of 0 if not all relevant measures were met 12 22. Mortality was all-cause mortality with information on vital status obtained from the Danish Civil Registration System.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marginal cases with an atypical presentation, or premorbid nonindependent patients, may make stroke physicians direct patients to an emergency department instead of a stroke unit. The COVID-19 pandemic did affect stroke care in some countries, but based on earlier performed analysis indicating no effect on admission, reperfusion therapy rates, and quality of acute stroke care, it is unlikely that the pandemic affected the results of the current study (15,16).…”
Section: Discussionmentioning
confidence: 74%